Effects of density of sago/urea formaldehyde particleboard towards its thermal stability, mechanical and physical properties - Tay, Chen Chiang; Sinin, Hamdan; Mohd Shahril, Osman (Penerbit UTM Press, 2016)
This study examined the effect of density on the thermal stability, physical and mechanical properties of sago particleboard. Sago particles and Urea Formaldehyde (UF) were used as raw materials in the fabrication process. The fabrication and testing method were based on JIS A 5908 standard. The samples were prepared based on different desired density and went through a series of thermal stability, mechanical and physical tests. Mechanical properties of the composites were characterized by tensile, flexural, impact strength, screw test and internal bonding which had great influence on the particleboard performance. All the panels were tested for physical properties (water absorption and thickness swelling) to identify their use for indoor application. Thermal properties like thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) for the Sago/UF composites were analysed. The results showed particleboard with 800 kg/m3exhibited the optimum strength on Internal Bonding, Screw test, Bending and Flexure test. Particleboard with 700 kg/m3has better performance on Impact test. 500 kg/m3 showed better curing properties with DSC. TGA showed that all the Sago/UF particleboard decompose with single-stage and were decomposed into three main steps like water absorption, volatile and char.